Examining the Use of a Brief Online Intervention in Primary Care for Changing Low-Income Caregivers' Attitudes Toward Spanking. Issue 21 (November 2022) - Richardson, Hilary L.; Damashek, Amy
There is a robust and growing literature base indicating that spanking is a common, but potentially problematic, discipline strategy.Goals : Using a randomized controlled trial design, this study examined whether participation in a brief online program, Play Nicely, would result in favorable changes in caregivers' attitudes toward spanking. The study also examined whether the intervention was equally effective for participants of color (POC) and White participants, and it assessed caregivers' perceptions of the program's cultural sensitivity.Methods: Participants were 52 caregivers from 1- to 5-year-old children who were visiting a pediatric clinic. Participants were enrolled and randomly assigned to either engage in the Play Nicely online program ( n = 21) or view a control condition website ( n = 31) in a clinic exam room.Results: There was not a statistically significant difference between the treatment and control groups' scores on attitudes toward spanking (ATS) at post-test ( F (1, 49) = 1.515, p = 0.224), but a small between-group effect size was detected ( d = 0.20). Within the treatment condition, desired changes in ATS scores were significantly higher among White participants than POC ( t (17) = −2.125, p = 0.049), but there was not a significant difference in reported perceptions of Play Nicely's cultural acceptability between White participants and POC ( t (19) = 0.469, p = 0.644).Conclusions: Findings suggest a need for further investigation of Play Nicely's impact on caregivers' ATS with a larger sample to clarify the program's utility as a potential population-based tool for parent education and violence prevention. Additional research is needed to identify sociocultural factors that may moderate the effects of spanking interventions for families across diverse racial backgrounds.